Government spending in a growing economy: Fiscal policy and growth cycles - Jamee K. Moudud (Levy Economics Institute of Bard College, 1999)
Based on neoclassical theory, cutting budget deficits has come to be seen as a principal way to increase long-run growth, but the empirical evidence is ambiguous on the outcome of this macropolicy. A new model, the classical growth cycles (CGC) model, offers an alternative theoretical framework for analyzing the complex effects of fiscal policy. The CGC model holds that the impacts of fiscal policy on growth are transmitted through its effects on business profitability and the business saving rate. Investigation of both short-run and long-run effects of government spending and of the distinctive long-run effects of different types of government spending suggests that indiscriminate deficit cutting will not lead to a rise in the long-run profit rate and may exacerbate poverty and inequality in the short and the long run.
Keywords: 330